Decision system model for HC exploration on the basis of DST test results - Dubiel, Stanisław; Zubrzycki, Adam; Maruta, Michał (My University, 2013)
The paper presents the results of 57 Drill Stem Tests (DST) within the Upper Jurassic carbonate rocks forming the Carpathian Fordeep basement in the area between Bochnia and Ropczyce (south Poland) performed by the Polish Oil and Gas Company in the years 1993 to 1998. Designated prospective horizons were tested with DST for assessing productivity of strata. DST tests were performed mostly in open hole sections of boreholes (more rarely in cased holes) after prior borehole casing perforation operations. In approximately 75% cases the cycle drill stem tests (DST) was used for testing the Upper Jurassic carbonate rocks. On the basis of data and experiences obtained during exploration of the Upper Jurassic carbonate rocks the model of the work-flow decision diagram was elaborated. It may be used for the integrated HC field management and for possible modifications in the drilling and testing technology.
AGH Drilling, Oil, Gas
Keywords: petroleum explorations; HC reservoir assessment; Carpathian Foredeep basement; Upper Jurassic carbonate reservoir rocks; DST; tests results; model of the work-flow decision; HC field management